Attenuation of Myocardial Injury by HMGB1 Blockade during Ischemia/Reperfusion Is Toll-Like Receptor 2-Dependent - Jan Mersmann; Franziska Iskandar; Kathrina Latsch; Katharina Habeck; Vera Sprunck; René Zimmermann; Ralf R. Schumann; Kai Zacharowski; Alexander Koch (Hindawi Limited, 2013)
Genetic or pharmacological ablation of toll-like receptor 2 (TLR2) protects against myocardial ischemia/reperfusion injury (MI/R). However, the endogenous ligand responsible for TLR2 activation has not yet been detected. The objective of this study was to identify HMGB1 as an activator of TLR2 signalling during MI/R. C57BL/6 wild-type (WT) or TLR2−/−-mice were injected with vehicle, HMGB1, or HMGB1 BoxA one hour before myocardial ischemia (30 min) and reperfusion (24 hrs). Infarct size, cardiac troponin T, leukocyte infiltration, HMGB1 release, TLR4-, TLR9-, and RAGE-expression were quantified. HMGB1 plasma levels were measured in patients undergoing coronary artery bypass graft (CABG) surgery. HMGB1 antagonist BoxA reduced cardiomyocyte necrosis during MI/R in WT mice, accompanied by reduced leukocyte infiltration. Injection of HMGB1 did, however, not increase infarct size in WT animals. In TLR2−/−-hearts, neither BoxA nor HMGB1 affected infarct size. No differences in RAGE and TLR9 expression could be detected, while TLR2−/−-mice display increased TLR4 and HMGB1 expression. Plasma levels of HMGB1 were increased MI/R in TLR2−/−-mice after CABG surgery in patients carrying a TLR2 polymorphism (Arg753Gln). We here provide evidence that absence of TLR2 signalling abrogates infarct-sparing effects of HMGB1 blockade.